Multimedia Cognitive Wireless Sensor Network Cluster Routing based on Intelligent Robot Edge Computing and Collection (Informatica, 2024)
This paper proposes a clustering routing algorithm for multimedia cognitive wireless sensor networks based on edge computing and acquisition of intelligent robots. The routing protocol can realize the efficient aggregation and transmission of perceptual data in cognitive wireless sensor networks (CRSN. Cognitive wireless sensor networks), especially clustering routing protocols, can further reduce the complexity of route selection and improve the scalability of the network, which is very important for the overall performance of the network. Therefore, in this paper, we use intelligent robot edge computing and acquisition technology to study the communication problem of multimedia cognitive wireless sensor networks. Firstly, the edge calculation and acquisition system based on intelligent robot is established. The sensor data is collected and processed in real time by robot, and the data is transmitted and calculated in real time. Secondly, a clustering routing algorithm based on multimedia cognition is proposed to realize dynamic clustering and routing optimization of wireless sensor networks by comprehensively considering the signal strength and energy residual of network nodes. On this basis, a clustering routing strategy is proposed to divide network nodes into multiple clusters, which improves transmission efficiency and energy utilization. Finally, the effectiveness and superiority of the proposed algorithm are verified by comparative experiments, and the results show that the algorithm has achieved obvious effects in improving the network transmission efficiency and reducing the network energy consumption. This study provides a new idea and method for real-time transmission and calculation of multimedia cognitive wireless sensor networks.